Analisis Tingkat Kepuasan Terhadap NewLecturer di Universitas Indo Global Mandiri Dalam Mendukung Aktivitas Akademik - Angelina, Sirly; Dhamayanti; Marcellina, Dona (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
The development of information technology in the era of globalization has had a significant impact on various aspects of life, including education. The use of technology in education aims to facilitate academic management in higher education. Universitas Indo Global Mandiri utilizes this technology through an academic information system called NewLecturer. This system is designed to support lecturers in various academic activities such as filling in grades, viewing schedules, uploading learning materials, and printing Lecture Minutes (BAP). Previously, the Lecturer.uigm.ac.id system was used; however, it had limitations in sharing learning materials, so it required integration with the E-Learning System. With the launch of Newlecturer in the odd semester of the 2024/2025 academic year, lecturers can now access various academic services on one platform. However, since its implementation, there has been no measurement related to the level of lecturer satisfaction with the NewLecturer system. This study aims to analyze the quality and level of lecturer satisfaction with the system using the Technology Acceptance Model (TAM) approach. The results of the study are expected to provide valuable input for the evaluation and development of the NewLecturer system, aiming to improve the quality of academic services at Universitas Indo Global Mandiri.